Synthesis by solid route and physicochemical characterizations of blends of calcium orthophosphate powders and mesoporous silicon particles - Richard, Caroline; Alfred-Arulrasa, Mélissa; Ramadas, Harikrishnan; Mahagamage, Pubudu Tharanga; Defforge, Thomas; Gaultier, Gael; Autret-Lambert, Cécile; Poirot, Nathalie; Champion, Eric; Magnaudeix, Amandine (Frontiers in Bioengineering and Biotechnology, 2023)
The purpose of the study was to investigate the synthesis of economic calcium phosphate powders from recycled oyster shells, using a ball milling method. The oyster shell powder and a calcium pyrophosphate powder were used as starting materials and ball milled, then heat treated at 1050°C for 5 hours to produce calcium phosphate powders through a solid-state reaction. Electrochemically synthesized mesoporous silicon microparticles were then added to the prepared phosphate powders by mechanical mixer. The final powders were characterized using X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy to analyze their chemical composition and determine the most suitable process conditions. The biocompatibility of the produced powders was also tested in vitro using murine cells and the results showed good biocompatibility.